New Age: Spiritualitas Orang Perkotaan - Abdul Muis Naharong (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2009)
This article examines the phenomenon that occurs in the last two decades in the community in various parts of the world stricken by the fever of spirituality. The various forms of spirituality emerge. This phenomenon is so widely in the West that gave birth to the slogan “Spirituality, yes, Organized religion, no.” One of the movements of this spirituality is New Age, which is a combination of various teachings and practices. The uniqueness of this movement makes the scholars acknowledged that the New Age is difficult to describe. Abdul Muis Naharong tried to describe the New Age which spread to Eastern countries, including Indonesia, due to the globalization process. The spread of ideas and New Age practices take place primarily through the mediation of books imported from the West, and some studies centers established by institutions and individuals in this country.